The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/s0034-737x2014000100011
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade em população base de pimenteiras ornamentais (Capsicum annuum L.)

Abstract: O objetivo deste trabalho foi caracterizar progênies de uma população base de pimenteiras (Capsicum annuum L.). Foram utilizadas 54 plantas de uma geração F2 de pimenteiras ornamentais, para se avaliarem os seguintes caracteres morfoagronômicos: altura da planta (AP), diâmetro da copa (DDC), altura da primeira bifurcação (APB), diâmetro do caule (DCL), comprimento da folha (CFL), largura da folha (LFL), comprimento da corola (CDC), comprimento de antera (CANT), comprimento do estilete (CES) e largura da pétala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
2
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 7 publications
3
10
2
3
Order By: Relevance
“…Plants with the highest mean values for stem diameter, such as accessions UFPB 099, UFPB 137 and UFPB356, are recommended for selection. Nascimento et al (2011) and Neto et al (2014) when working with ornamental pepper found results similar to this paper's, indicating for selection genotypes that presented the highest mean values for this trait. This character is important in the selection of genotypes since the stem diameter must be large enough to support the weight of the plant and the fruits (Ferreira et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Plants with the highest mean values for stem diameter, such as accessions UFPB 099, UFPB 137 and UFPB356, are recommended for selection. Nascimento et al (2011) and Neto et al (2014) when working with ornamental pepper found results similar to this paper's, indicating for selection genotypes that presented the highest mean values for this trait. This character is important in the selection of genotypes since the stem diameter must be large enough to support the weight of the plant and the fruits (Ferreira et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…Taking this into consideration, accessions UFPB001, UFPB003, UFPB004, UFPB45 and UFPB099 are indicated for the selection, because they present larger flowers; also accession UFPB003 and the cultivar Calypso, because they presented the largest petals. Neto et al (2014) and Fortunato et al (2015) found similar results for variability in flower characters in pepper. These results indicate that there are different sized flowers among the genotypes and the one with the largest flowers can be selected.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Os capsaicinoides [1] presentes nessas espécies são representados por nornorcapsaicina, norcapsaicina, homocapsaicina, nornordiidrocapsaicina, capsaicina [2], hordiidrocapsaicina, diidrocapsaicina [3] e homodiidrocapsaicina (4). O metabólito mais importante desse gênero é a capsaicina [2], sendo conhecida por três propriedades principais, sendo elas anti-inflamatória, antioxidante e potencial liberador de endorfina (5,6).…”
Section: Introductionunclassified